2019
DOI: 10.1590/s1677-5538.ibju.2018.0246
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of surgical complications of nephrectomy for urolithiasis

Abstract: Objectives: Nephrectomy due to stone disease may be a challenging procedure owing to the presence of significant inflammation and infection, involving high complication rate. The objective of our study was to identify predictors for complications of nephrectomy for urolithiasis. Patients and Methods: A retrospective review of 149 consecutive patients > 18y submitted to simple nephrectomy for urolithiasis from January 2006 to July 2012 was performed. Clinical data, compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 20 publications
(24 reference statements)
3
13
0
3
Order By: Relevance
“…No unnoticed intestinal lesion was reported in this series, as compared to other revised studies. (3,9,15) In this study, grade II complications prevailed, as in other investigations that report a prevalence of minor complications (grade I, II). (3,15,20) Al-Otaibi et al (18) reported two grade V (0.48%) complications, one as the result of the perforation of the duodenum complicated with septic shock and another due to pulmonary thromboembolism.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…No unnoticed intestinal lesion was reported in this series, as compared to other revised studies. (3,9,15) In this study, grade II complications prevailed, as in other investigations that report a prevalence of minor complications (grade I, II). (3,15,20) Al-Otaibi et al (18) reported two grade V (0.48%) complications, one as the result of the perforation of the duodenum complicated with septic shock and another due to pulmonary thromboembolism.…”
Section: Discussionsupporting
confidence: 72%
“…However, when performing the lumboscopic approach in adulthood in patients who underwent open surgery during childhood, we have observed that access to the retroperitoneum is easier, the perirenal tissue is laxer and an appropriate workspace can be created. (9,10) Renal percutaneous surgery also causes adhesions from the renal unit to the perirenal, which can extend up to the renal hilum. This is the reason some authors recommend the transperitoneal approach in patients with a past history of this surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Approaches to the rehabilitation process in comorbid patients should be different from standard rehab programs, since the body's response to the standard load in such patients may be inadequate, hence the need for an active search of highly specific markers and valid methods of risk stratification for cardiovascular events (CVE) in the presence of multimorbid conditions. This requires a weighted integrated approach with an estimate of total risk [22][23][24]. In this plan, the Charlson comorbidity index and the six-minute walking test seem promising as rather universal combinations of assessment of degree of comorbidity and exercise tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of urinary stone disease has signifi cantly increased worldwide in the last decades, with an overall prevalence of 7% to 12% (1)(2)(3)(4). In Brazil, the number of stone-related hospitalizations increased from 58.165 in 1998 to 67.306 in 2012 (5,6). As the disease becomes more prevalent, there is an increase in patient's interest which is translated in a rise on the volume of search for information regarding the matter globally (7).…”
Section: Introductionmentioning
confidence: 99%